Analisis Kualitas Layanan Internet Xl Axiata Menggunakan Servqual, NPS, dan Dashboard Monitoring di Kota Tegal - Dede Gunawan; Sarif Surorejo; Nugroho Adhi Santoso (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
This study evaluates the quality of XL Axiata internet services in Tegal City, measures customer loyalty, and develops a monitoring dashboard to present survey findings in an integrated form. The research used a quantitative descriptive approach with primary data collected through an online questionnaire distributed to XL Axiata users in Tegal City. A total of 304 responses were analyzed. Service Quality was assessed using five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. In this study, SERVQUAL was operationalized through users’ perceptions of received services without measuring expectations, so the analysis describes perceived service performance rather than an expectation–perception gap. Customer loyalty was measured using Net Promoter Score (NPS) and classified into promoter, passive, and detractor groups. The findings show an overall service-quality mean of 4.000, indicating a fairly good condition. The highest-rated indicators concern understanding customer needs and service security, while the lowest ratings concern complaint handling, network disruptions, and network stability. The NPS was 24.0, with 38.5% promoters, 47.0% passives, and 14.5% detractors. A dashboard was then designed with interactive filters for gender, subdistrict, and customer status, together with summary indicators and visualizations of Service Quality and loyalty. The results indicate that service improvement should prioritize complaint handling and network consistency while maintaining the aspects already perceived positively.